Effects of anabolic-androgens on brain reward function - Mhillaj, Emanuela; Morgese, Maria Grazia; Tucci, Paolo; Bove, Maria; Schiavone, Stefania; Trabace, Luigia (Frontiers in Neuroscience, 2015)
Androgens are mainly prescribed to treat several diseases caused by testosterone deficiency. However, athletes try to promote muscle growth by manipulating testosterone levels or assuming the so called androgen anabolic steroids (AAS). These substances were originally synthesized to obtain anabolic effects greater than testosterone. Although AAS are rarely prescribed compared to testosterone, the off-label utilization is very wide. Furthermore, combination of different steroids, and doses largely higher than those used in therapy are common. Symptoms of the chronic use of supra-therapeutic doses of AAS include anxiety, depression, aggression, paranoia, distractibility, confusion, amnesia. Interestingly, some studies have shown that AAS elicited electroencephalographic changes similar to those observed with amphetamine abuse. Among the AAS abusers, the frequency of side effects is higher, with psychiatric complications such as labile mood, lack of impulse control and high violence. On the other hand, AAS addiction studies are complex because the collection of data is very difficult due to reticent subjects and can be biased by many variables, including physical exercise, that alter the reward system. Moreover, it has been reported that AAS may imbalance neurotransmitter systems involved in reward process, leading to an increased sensitivity toward opioid narcotics and central stimulants. The aim of this review is to discuss what is present in literature in regard to steroid abuse and alteration of reward system in preclinical and clinical studies.